নাই বা হলো পারে যাওয়া - চৌধুরী, কবীর, ১৯২৩-২০১১. (ঢাকা : সাহিত্য প্রকাশ, 2007)
Autobiography of a 20th century Bengali author, translator, college teacher, and retired government official from Bangladesh.
1. Śaiśaba-kaiśora, prathama yaubana, 1923-1945 -- 2. Cākarijībana : praśāsanika kāla, 1945-1955 -- 3. Śikshakatā o lekhālekhira kāja, 1955-1971 -- 4. Deśa o bideśe ānatarjātika sammelana kāla, 1972-2004 -- 5. Jībanera nānā ghaṭanā, 1985-2004 -- 6. Sāhityika-sāmājika-sāṃskrti̥ka-pāribārika kājakarmera kathā, 2005-2006 -- 7. Belāśeshera kathakatā
Donated By Akbar Ali Khan
In Bengali.
Keywords: Chowdhury, Kabir, -- 1923-2011.; Authors, Bengali -- Bangladesh -- Biography; Authors, Bengali -- 20th century -- Biography; College teachers -- Bangladesh -- Biography; Translators -- Bangladesh -- Biography; Bangladesh -- Officials and employees, Retired -- Biography